The Influence of Destination Image on Visitor Satisfaction - Rudi Setiawan; Umi Narimawati; Juanim (Journal of Science and Education (JSE), 2025)
This study aims to determine the effect of destination image on visitor satisfaction in tourist villages in Ciamis Regency and Pangandaran Regency. Data were collected through questionnaires and analyze using a quantitative approach with the help of SPSS. The results showed that destination image had a positive and significant effect on visitor satisfaction, with the Social Setting and Environment dimension having the greatest effect, while Natural and Cultural Resources had the least effect. These findings contribute to the development of academic studies on tourism and provide practical input for managers and local governments in improving destination quality.